Local microglial activation induced and labeled in the retina in a novel subretinal hemorrhage mouse model - Boglárka Balogh; Marietta Zille; Gergely Szarka; Loretta Péntek; Anett Futácsi; Béla Völgyi; Tamás Kovács-Öller (Scientific Reports)
Abstract Subretinal hemorrhage (SRH) is caused by the accumulation of blood between the neurosensory retina and the retinal pigment epithelium or between the retinal pigment epithelium and the choroid. SRH often arises from age-related macular degeneration, traumas, and may occur spontaneously caused by other diseases like hypertension and diabetes. Here, we developed a novel technique - co-injection of blood and a dye-coupled tracer protein, Cholera toxin subunit B (CtB) - to better localize and understand the disease and how it can cause microglial activation, inflammation, and partial vision loss. Our results show that microglia are activated in the inner retinal layers in zones adjacent to blood injection. In contrast, the non-affected zone of the injected eye showed no microglial activation. For the first time, we used phosphate-buffered saline (PBS) injections as a control to assess the specific effects of injected blood. The results demonstrated that blood induced a markedly stronger activation response in the surrounding tissue, whereas PBS elicited a comparatively milder effect. PBS did cause microglial activation, but it was largely confined to the injection site and adjacent regions, and to a lesser extent than that observed with blood. We also observed microglial activation in the inner retina, along with the emergence of microglia and macrophages in the retinal pigment epithelium. Using advanced imaging techniques, we were able to better localize the affected area which comprises not only the immediate retinal area over the blood clot but the neighboring regions as well. These findings will provide the basis for novel therapeutic interventions targeting neuroinflammation in the retina after subretinal hemorrhage and other diseases affecting the eye.